(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The article discusses the issues of climate comfort assessment in mountainous terrain, the complexity of which requires a spatio-temporal study. Vayots Dzor, which is a typical mountainous area, is chosen as an example in the article. Here there is the necessary variety of interrelated climatic conditions, the level of importance, which together make Vayots Dzor a typical object of geoecological research. Such research is not only of scientific and methodological interest and is useful for the study of climate comfort in other mountain areas, but also with its practical orientation can contribute to the scientific understanding and solution of the spatial planning problem of Vayots Dzor. The aim of the study is to develop a methodology and methodological approaches for the geoecological integral assessment of the climatic comfort of the Vayots Dzor area, based on the measurability and analysis of the bioclimatic component of its natural resources potential, using integral bioclimatic indicators. The article presents the results of the calculation and analysis of the spatial-temporal distribution of bioclimatic resources of Vayots Dzor. Equivalent effective temperature, radiative equivalent effective temperature, discomfort coefficient and weather severity were used as the main bio-climatic indices. As a result of the study, some features of the climatic conditions of the area during the last decades were revealed, climatic comfort zones and their territorial distribution in different periods of the year were distinguished. It was found that the distribution of calculated bioclimatic resources in the Vayots Dzor area has significant spatial and temporal heterogeneity, and is also characterized by the formation of small areas, which are caused by local atmospheric circulation processes.